2016
DOI: 10.3389/fnana.2016.00084
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of the Cingulum Bundle in the Human Brain: A New Perspective Based on DSI Tractography and Fiber Dissection Study

Abstract: The cingulum bundle (CB) is a critical white matter fiber tract in the brain, which forms connections between the frontal lobe, parietal lobe and temporal lobe. In non-human primates, the CB is actually divided into distinct subcomponents on the basis of corticocortical connections. However, at present, no study has verified similar distinct subdivisions in the human brain. In this study, we reconstructed these distinct subdivisions in the human brain, and determined their exact cortical connections using high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 74 publications
(106 reference statements)
3
97
0
2
Order By: Relevance
“…Moreover, we did not parse the nominal pathways into their respective subdivisions. For example, we neither distinguished between subgenual and retrosplenial subdivisions of CB (Jones et al, ; Wu et al, ), nor the three subdivisions of the UF (Bhatia et al, ). Future attempts at identifying subdivisions within pathways may help improve the specificity of tractographic analysis and help delineate which gray matter areas are directly affected by DBS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not parse the nominal pathways into their respective subdivisions. For example, we neither distinguished between subgenual and retrosplenial subdivisions of CB (Jones et al, ; Wu et al, ), nor the three subdivisions of the UF (Bhatia et al, ). Future attempts at identifying subdivisions within pathways may help improve the specificity of tractographic analysis and help delineate which gray matter areas are directly affected by DBS.…”
Section: Discussionmentioning
confidence: 99%
“…The CAB is connected with brain regions underlying both higher-order cognitive functioning and emotion processing and implicated in neurodegeneration pathology [41]. Moreover, associations have been reported between CAB integrity and functioning in episodic memory, decision-making, and executive control [42,43]. The CAB has also been shown to directly connect the posterior cingulate cortex and the subiculum of the hippocampus [44], both of which are critical nodes in the default mode network shown to be altered in PTSD [1,45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported reduced ACC activation [Kana et al, ] and aberrant frontoā€ACC FC in ASD during inhibitory control tasks [Kana et al, ; Padmanabhan et al, ; Solomon et al, ]. Ikuta et al [] reported reduced fractional anisotropy in the cingulum bundle, which connects frontal, temporal and parietal regions [Wu et al, 2016]. Taken together, this suggests that IFJā€dACC FC may be a locus of dysregulation in children with ASD and should be a focus of future studies of inhibitory control in children with the disorder.…”
Section: Discussionmentioning
confidence: 86%